Caught in the Scroll: A Psycholinguistic Exploration of FOMO and Viral Language Among Gen Z on Social Media - Saleh, Eliza Farahdiba; Sarjit Singh, AP. Dr. Manvender Kaur A/P (Lembaga Sembilan Tiga Community, 2025)
This study examines the psycholinguistic aspects of the FOMO, or Fear of Missing Out, phenomenon in the context of viral language on social media, especially TikTok, Instagram, and X, formerly known as Twitter. Generation Z, born in the digital era, shows strong emotional and behavioural responses to viral content. With a qualitative approach, this study analyses multimodal texts such as captions, hashtags, audio, and visual elements that give rise to a sense of urgency, social inclusion, and emotional resonance. The results show that viral language patterns, when combined with synchronous visual and audio elements and celebrity influence, significantly trigger FOMO-based engagement. In addition, parasocial relationships and cultural validation play an important role in shaping users' behaviour, especially in the K-pop fan community. This study provides psycholinguistic insights into how language on social media is processed, internalised, and replicated by Gen Z audiences. In conclusion, critical awareness is needed regarding the psychological impact of viral discourse and its influence on identity formation and digital well-being